Environmental Health and Behavioral Factors Associated with the Incidence of Diarrhea in Children: A Scoping Review - Devanty Yuliana; Budiyono Budiyono; Yusniar Hanani Darundiati (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Diarrhea remains a major public health problem among children under five years of age and is closely associated with poor environmental sanitation, inadequate hygiene behavior, and limited access to clean water. Objective: This study aimed to identify and synthesize evidence regarding environmental and behavioral factors contributing to diarrhea incidence in infants and toddlers. Method: A scoping review approach was applied by searching articles in PubMed, ScienceDirect, and Scopus using keywords related to diarrhea, sanitation, hygiene, water quality, drinking water, and environmental health. Articles published from 2019 to 2025 were screened, resulting in 14 eligible studies from 6,484 identified articles. Result and Discussion: Environmental conditions and hygiene behavior contribute to fecal contamination pathways that increase diarrhea risk. Improving sanitation, promoting proper hygiene practices, and ensuring access to safe water are essential and interconnected prevention measures. Conclusions: Diarrhea incidence in children under five is influenced by environmental, behavioral, and clean water management factors